Ultra-processed food consumption is associated with increase in fat mass and decrease in lean mass in Brazilian women: A cohort study - Rudakoff, Lívia Carolina Sobrinho; Magalhães, Elma Izze da Silva; Viola, Poliana Cristina de Almeida Fonseca; de Oliveira, Bianca Rodrigues; da Silva Coelho, Carla Cristine Nascimento; Bragança, Maylla Luanna Barbosa Martins; Arruda, Soraia Pinheiro Machado; Cardoso, Viviane Cunha; Bettiol, Heloisa; Barbieri, Marco Antonio; Levy, Renata Bertazzi; da Silva, Antônio Augusto Moura (Frontiers in Nutrition, 2022)
Objective: To investigate the association between ultra-processed food (UPF) consumption at 23-25 years of age and measurements of body composition – fat mass (FM), fat mass and lean mass (LM) distribution – at 37-39 years of age in Brazilian adults. Methods: 1978/1979 birth cohort study conducted with healthy adults from Ribeirão Preto, São Paulo, Brazil. A total of 1,021 individuals participated in the FM analysis and 815 in the LM analysis and FM distribution. Food items were grouped according to the NOVA classification. UPF consumption was expressed as a percentage of total daily intake (g/day). Linear regression models were used to estimate the effect of UPF consumption (g/day) on body mass index (BMI), body fat percentage (BFP), fat mass index (FMI), android fat (AG), gynoid fat ( GF), android-gynoid fat ratio (AGR), lean mass percentage (LMP), lean mass index (LMI) and appendicular lean mass index (ALMI). Marginal plots were produced to visualize interactions. Results: The mean daily UPF consumption in grams was 35.8% (813.3 g). There was an association between UPF consumption and increase in BMI, BFP, FMI, AG and GG and decrease in LMP, only in women. Conclusion: A high UPF consumption is associated with a long-term increase in FM and a decrease in LM in adult women.